Development of a Brief Survey on Colon Cancer Screening Knowledge and Attitudes Among Veterans - Franklin Medio, PhD; Dachao Liu, MA; June Lee; Marian Fitzgibbon, PhD; Terry C. Davis, PhD; Nancy C. Dolan, MD; M. Rosario Ferreira, MD; Alfred Rademaker, PhD; Charles L. Bennett, MD, PhD; Michael S. Wolf, PhD, MPH (Centers for Disease Control and Prevention, 2005)
Introduction Poor knowledge of and negative attitudes toward available screening tests may account in part for colorectal cancer screening rates being the lowest among 17 quality measures reported for the Department of Veterans Affairs health care system, the largest integrated health system in the United States. The purpose of this study was to develop a brief assessment tool to evaluate knowledge and attitudes among veterans toward colorectal cancer screening options. Methods A 44-item questionnaire was developed to assess knowledge, attitudes, and beliefs about colorectal cancer and screening and was then administered as part of an ongoing randomized controlled trial among 388 veterans receiving care in a general medicine clinic. Sixteen candidate items on colorectal cancer knowledge, attitudes, and beliefs were selected for further evaluation using principal components analysis. Two sets of items were then further analyzed. Results Because the Cronbach a for beliefs was low (a = 0.06), the beliefs subscale was deleted from further consideration. The final scale consisted of seven items: a four-item attitude subscale (a = 0.73) and a three-item knowledge subscale (a = 0.59). Twelve-month follow-up data were used to evaluate predictive validity; improved knowledge and attitudes were significantly associated with completion of flexible sigmoidoscopy (P = .004) and completion of either flexible sigmoidoscopy or colonoscopy (P = .02). Conclusion The two-factor scale offers a parsimonious and reliable measure of colorectal cancer screening knowledge and attitudes among veterans. This colorectal Cancer Screening Survey (CSS) may especially be useful as an evaluative tool in developing and testing of interventions designed to improve screening rates within this population.